Draft Annual Plan 1987-88 Vol. II Sectoral Profile Government of Uttar Pradesh, Planning Department - Planning Commission (Planning Commission, 1986)
Uttar Pradesh has rich natural resources for the development of agriculture upon which the economy of the State is largely dependent. About 78 per cent of the total working force, as against 72 per cent in the country,' is engaged in agriculture and allied activities!. Due to heavy pressure of population in rural areas and limited opportunities of employment in non-agricultural activities, accelerated development in the agricultural sector assumes added importance. Foodgrains comprise the most important item of agricultural produce and all out efforts have been made to increase their production. During the Sixth Plan, against a target of 280 lakh tonnes, the level of foodgrain production at the end of 1984-85 reached 299.18 lakh tonnes.
Sectoral Profile
Government of Uttar Pradesh